Nanophytosome delivery system and in vivo test of combination of binahong leaf extract (Andredera cordifolia) and bay leaf (Syzygium polyanthum) as a diabetic wound healer - Arip Saifurrohman; Garnadi Jafar; Entris Sutrisno; Fathurahman Ari Senjaya (Science Midwifery, 2026)
This study aimed to develop and characterize a nanophytosome system containing combined extracts of bay leaf (Syzygium polyanthum) and binahong leaf (Anredera cordifolia), and to evaluate its wound healing activity through in vivo study. The extracts were prepared by maceration using 96% ethanol and characterized through phytochemical screening and LC-MS/MS analysis. Nanophytosomes were formulated using phospholipid complexes with variations of surfactants, followed by homogenization and sonication. The formulations were evaluated for particle size, polydispersity index, zeta potential, and entrapment efficiency. The results showed that particle size ranged from 16.30 to 927.18 nm, with the smallest size observed in Tween 80-based formulation. The polydispersity index ranged from 0.20 to 0.86, indicating better homogeneity in Tween 80 systems. Zeta potential values ​​were in the range of −6 to −17 mV, suggesting moderate stability. Entrapment efficiency was high in all formulations (92.5–97.3%), with the highest value observed in Cremophor-based formulation. In vivo evaluation demonstrated that the nanophytosome significantly accelerated wound healing compared to control groups, as indicated by faster wound contraction and improved tissue regeneration. In conclusion, the nanophytosome system enhanced the physicochemical properties and delivery of bioactive compounds, showing potential as an effective therapeutic approach for wound healing.